Efektivitas Penggunaan E-Modul PAI-PTU Sebagai Bahan Pembelajaran Mandiri - Nina Ikhwati Wahidah; Iskandar Iskandar; Agus Komarudin (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study was to see the effectiveness of using the PAI-PTU e-module for independent learning for students of the Faculty of Science and Technology, Nahdlatul Ulama University, Lampung. The research method used is a quasi-experimental, this research is classified as pre-experimental research. One group pretest and posttest to see the improvement of student learning outcomes before and after using PAI-PTU e-module learning materials as independent learning materials. The sample in this study were 100 students obtained by random sampling. The result of this study is the use of the PAI-PTU e module as an independent learning material can be seen from the results of the paried t-test, based on the results of the paired t-test, the 2-tailed significance is 0.000 < 0.05, because the 2-tailed significance result is smaller. of 0.05, it can be concluded that there is a significant difference between the results of the pretest and posttest of the use of the pai-ptu e-module at Nahdlatul Ulama University Lampung. Next for the t-count value is 13,554, then for the t table with df 99 it is 1,984. Then it can be seen that the t count is 13,554 > 1,984 t table, so it can be concluded that there is a significant difference from the pretest results before using the pai-ptu e-module learning material with the posttest results after using the pai-ptu e-module.